Leg over Leg : Volume Two - Shidyāq, Aḥmad Fāris, 1804?-1887 (Book collections on Project MUSE., 2013)
Leg over Leg recounts the life, from birth to middle age, of 'the Fariyaq, ' alter ego of Ahmad Faris al-Shidyaq, a pivotal figure in the intellectual and literary history of the modern Arab world. The always edifying and often hilarious adventures of the Fariyaq, as he moves from his native Lebanon to Egypt, Malta, Tunis, England and France, provide the author with grist for wide-ranging discussions of the intellectual and social issues of his time, including the ignorance and corruption of the Lebanese religious and secular establishments, freedom of conscience, women's rights, sexual relatio.